The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1086/509734
|View full text |Cite
|
Sign up to set email alerts
|

Methane and Ethane on the Bright Kuiper Belt Object 2005 FY9

Abstract: The spectrum of the bright Kuiper Belt object 2005 FY9 from 0.34 to 2.5 m is dominated by the red coloring of many outer solar system objects in the optical wavelength regime and by absorption due to methane in the near-infrared. The solid methane absorption lines are significantly broader on 2005 FY9 than on any other solar system body, indicating long optical path lengths through the methane. These long path lengths can be parameterized as a methane grain size of approximately 1 cm in a Hapke reflectance mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 29 publications
(37 reference statements)
5
100
0
Order By: Relevance
“…Binary ETNOs have not yet been discovered, but Sedna (Brown et al 2004b) and 474640 (Fraser and Brown 2012) have been observed with the Hubble Space Telescope and no close companions have been reported yet. In addition, most ETNOs are perhaps too faint to be observed by adaptive optics on even the largest existing ground-based telescopes, although detection biases favour the discovery of wide binaries.…”
Section: Fragmentation Versus Binary Dissociation: Wherementioning
confidence: 99%
“…Binary ETNOs have not yet been discovered, but Sedna (Brown et al 2004b) and 474640 (Fraser and Brown 2012) have been observed with the Hubble Space Telescope and no close companions have been reported yet. In addition, most ETNOs are perhaps too faint to be observed by adaptive optics on even the largest existing ground-based telescopes, although detection biases favour the discovery of wide binaries.…”
Section: Fragmentation Versus Binary Dissociation: Wherementioning
confidence: 99%
“…The average albedo is estimated to be p v = 0.71 +0.08 −0.02 (Ortiz et al 2012), which is in agreement with the estimation from the thermal data (Lim et al 2010). Spectroscopic observations of Makemake have revealed strong absorption bands associated with methane (Barkume et al 2005;Licandro et al 2006;Brown et al 2007;Tegler et al 2007Tegler et al , 2008. Brown et al (2007) reported the presence of ethane features and no apparent evidence for N 2 and CO. Tegler et al (2007Tegler et al ( , 2008 reported a small shift of the CH 4 bands in their spectra of Makemake in comparison with a model fit, suggesting the presence of trace amounts of N 2 ice.…”
Section: (136472) Makemakementioning
confidence: 99%
“…Spectroscopic observations of Makemake have revealed strong absorption bands associated with methane (Barkume et al 2005;Licandro et al 2006;Brown et al 2007;Tegler et al 2007Tegler et al , 2008. Brown et al (2007) reported the presence of ethane features and no apparent evidence for N 2 and CO. Tegler et al (2007Tegler et al ( , 2008 reported a small shift of the CH 4 bands in their spectra of Makemake in comparison with a model fit, suggesting the presence of trace amounts of N 2 ice. The grain sizes of CH 4 ice in their modelling varied from 0.1 cm to 6 cm, and the best fit was obtained for a model entailing grains of two sizes (Tegler et al 2007(Tegler et al , 2008.…”
Section: (136472) Makemakementioning
confidence: 99%
See 1 more Smart Citation
“…The first one is constituted by TNOs whose spectra are dominated by methane-ice absorption bands, such as Pluto Protopapa et al 2008), Eris (Brown et al 2005;Licandro et al 2006b;Dumas et al 2007), and Makemake (Licandro et al 2006a;Brown et al 2007;Tegler et al 2007;Tegler et al 2008). A similar spectrum is also shown by Triton (Cruikshank et al , 2000Quirico et al 1999), probably an originally isolated TNO that was then captured by Neptune (McKinnon et al 1995).…”
Section: Introductionmentioning
confidence: 99%